Synthesis and Electrochemical and In Situ Spectroelectrochemical Characterization of Chloroindium(III) and Chloromanganese(III) Phthalocyanines Bearing 4-((4'-Trifluoromethyl)phenoxy)phenoxy Substituents - KOCA, ATIF (WILEY-V C H VERLAG GMBH, 2012)
The synthesis of novel tetra-substituted manganese and indium phthalocyanines was achieved by cyclotetramerization of corresponding phthalonitrile derivative. The new compounds have been characterized by using UV-vis, IR, 1H NMR and mass spectroscopic data. Spectroelectrochemical characterization of an indium phthalocyanine complex was performed for the first time in this paper and its electrochemical and spectroelectrochemical responses were compared with manganese phthalocyanine, bearing a redox active metal center. Electrochemical and spectroelectrochemical measurements exhibit that incorporation of redox active metal ion, MnIII, instead of InIII into the phthalocyanine core extends the redox capabilities of the complex including the metal-based reduction couples of the metal center and affect the aggregation behavior of the complexes. Presence of molecular oxygen in the electrolyte system affects the voltammetric and spectroelectrochemical responses of the phthalocyanines due to the interaction between the complexes and molecular oxygen. MnPc and InPc formed mu-oxo species and this reaction changed the electrochemical and optic responses of the complexes, which are desired properties for sensor and electrocatalytic applications of a material. An in situ electrocolorimetric method has been applied to investigate the color of the electro-generated anionic and cationic forms of the complexes for possible electrochromatic applications and for clarify the interaction mechanism of the MnPc with molecular oxygen.
Keywords: Electrochemistry; Indium; Manganese; Phthalocyanine; Spectroelectrochemistry; EXCITED-STATE DYNAMICS; MANGANESE PHTHALOCYANINE; ELECTROCATALYTIC PROPERTIES; COBALT PHTHALOCYANINES; OXYGEN REDUCTION; METAL SENSOR; METALLOPHTHALOCYANINES; COMPLEXES; BEHAVIOR; GOLD